2015
DOI: 10.1155/2015/732450
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Enhance Macrophages Polarization into M1 Phenotype through Activating RAGE/NF-κB Pathway

Abstract: Atherosclerotic lesions are accelerated in patients with diabetes. M1 (classically activated in contrast to M2 alternatively activated) macrophages play key roles in the progression of atherosclerosis. Since advanced glycation end products (AGEs) are major pathogenic factors and active inflammation inducers in diabetes mellitus, this study assessed the effects of AGEs on macrophage polarization. The present study showed that AGEs significantly promoted macrophages to express IL-6 and TNF-α. M1 macrophage marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
120
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 40 publications
5
120
0
2
Order By: Relevance
“…Synthetic ALE could increase the expression of IL-6, IL-8, MCP-1, and iNOS in induced THP-1 monocytes32. Furthermore, AGEs enhanced BMDM cells polarization into M1 macrophage with producing IL-6 and TNF-a proinflammatory cytokines and upregulating the expressions of CD11c and CD86 through activating RAGE/NF-κB pathway in mice33. In addition, AGEs has been shown to induce autophagy in some cells, such as hepatic stellate cells34, cardimyocytes35, vascular smooth muscle cells36, and endothelial cells37.…”
Section: Discussionmentioning
confidence: 92%
“…Synthetic ALE could increase the expression of IL-6, IL-8, MCP-1, and iNOS in induced THP-1 monocytes32. Furthermore, AGEs enhanced BMDM cells polarization into M1 macrophage with producing IL-6 and TNF-a proinflammatory cytokines and upregulating the expressions of CD11c and CD86 through activating RAGE/NF-κB pathway in mice33. In addition, AGEs has been shown to induce autophagy in some cells, such as hepatic stellate cells34, cardimyocytes35, vascular smooth muscle cells36, and endothelial cells37.…”
Section: Discussionmentioning
confidence: 92%
“…In its turn, protein kinase C is responsible for the activation of NF-kB [17] contributing to improvements in adhesion of monocytes to the vascular wall [17,18] . Jin et al [19] found that AGEs not only predominantly induce macrophages to secrete inflammatory cytokines, but also induce M1 polarization. Moreover, AGEs activate the RAGE/NF-kB pathway, whereas the blockade of RAGE or NF-kB can attenuate macrophage activation [19,20] .…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al [19] found that AGEs not only predominantly induce macrophages to secrete inflammatory cytokines, but also induce M1 polarization. Moreover, AGEs activate the RAGE/NF-kB pathway, whereas the blockade of RAGE or NF-kB can attenuate macrophage activation [19,20] . We also found a direct correlation between the levels of HbA1c and TNF-α in patients with newly diagnosed diabetes [ Figure 1].…”
Section: Discussionmentioning
confidence: 99%
“…Именно ПКС ответ ственна за активиза-цию NFκB способствующего повышению адгезии моноцитов к сосудистой стенке и их дифференци-ровке в макрофаги. Вместе с тем, образующиеся в условиях гипергликемии конечные продукты нефер-ментного гликирования (КПНГ), подавляют противо-воспалительную активность ядерных рецепторов PPARɣ [13], что доказывается выраженным противо-воспалительным эффектом агонистов PPARɣ [14].…”
Section: результатыunclassified